An upscaling of methane emissions from Swedish flooded land - Mike Peacock; Martyn N. Futter; William Lidberg; Mattias Lundblad; Pia Geranmayeh (Carbon Management)
The 2019 IPCC Refinement updated reporting guidelines for greenhouse gas (GHG) emissions (predominantly methane; CH4) from “flooded land”; reservoirs, ponds, and drainage ditches/canals. These waterbodies are created by humans and thus their GHG emissions are considered anthropogenic. Here, we consider the implications of accounting for flooded land emissions in the Swedish national GHG inventory. We collate relevant Swedish GHG data for reservoirs, ponds and ditches, and combine these, and IPCC emission factors (EFs), with estimates of total waterbody surface area to upscale emissions. We find flooded lands emit a national total of 34,000 t CH4 yr−1 using IPCC EFs, or 14,000 t CH4 yr−1 when using EFs derived from Swedish data only, equivalent to 19% and 8% of national CH4 emissions. Cumulatively, reservoirs cover the largest surface area (71% of total flooded land), followed by ditches (26%) and ponds (3%). However, using IPCC EFs, ditch emissions dominate the budget, emitting 28,700 t CH4 yr−1 compared to ∼1,700 t CH4 yr−1 for ponds and 3,400 t CH4 yr−1 for reservoirs. Our findings show that ditches may make outsized contributions to national emissions, and that default IPCC EFs may be inappropriately high for GHG accounting in Sweden, and presumably other northern nations.